AUTOMATION OF A 3D PRINTED HAND PROSTHESIS WITH ARDUINO APPLICATION - Lincon de Oliveira, Cristoffer (2021)
This study deals with the analysis of an automation method for a functional hand prosthesis. The possibility of adapting to a prosthesis manufactured by the 3D printing process that originally moved mechanically was evaluated, with the aim of automating this artifact and making it functional. It was idealized to develop an automation system for this type of prosthesis, so that obtaining by the additive manufacturing method is quick and easy, and is suitable to receive the customized automation system and accessible to users. After all the modeling and confection processes were completed, the Arduino® software with C / C ++ language was used, developing the programming for the prosthesis. The program was created with the function of performing reading by electromyography sensors (EGM), which has the function of capturing the action potentials produced by muscle fibers of the arm and its contraction, and sending this captured data to the Arduino® board, which then sends a signal to the micro motors, responsible for moving the arms. fingers. It was possible to manufacture the prosthesis, as planned and projected on a computer design platform, performing automation, testing the degree of movement qualitatively. Satisfactory results were obtained in its production and adequacy of automation at the prototype level. as planned and projected on a computational design platform, performing automation, testing the degree of movement qualitatively. Satisfactory results were obtained in its production and adequacy of automation at the prototype level. as planned and projected on a computational design platform, performing automation, testing the degree of movement qualitatively. Satisfactory results were obtained in its production and adequacy of automation at the prototype level.